Efektivitas Pengemasan Vakum dan Penyimpanan Dingin terhadap Umur Simpan Cabai Rawit (Capsicum frutescens L.) - Andi Ralle; St Sabahannur; Suraedah Alimuddin; Annisa Dwizahra (Universitas Pattimura, 2025)
Cayenne pepper (Capsicum frutescens L.) is a widely cultivated horticultural commodity in Indonesia, but its short postharvest shelf life presents limits marketability due to rapid quality deterioration during storage. This study evaluated the effects of packaging methods and storage temperatures on the shelf life and quality of cayenne pepper. A randomized complete block design with a two-factor factorial arrangement was employed. The first factor was packaging (no packaging, non-vacuum packaging, and vacuum packaging), and the second was storage temperature (5 °C ± 1 °C, 7 °C ± 1 °C, and 9 °C ± 1 °C). The results showed that the combination of vacuum packaging and storage at 5 °C yielded the best outcome, with the longest shelf life of up to 61.67 days, the lowest weight loss of 7.33%, and preserved cayenne pepper quality, as indicated by a vitamin C content of 1.44 mg/100 g, optimal deep red color (score 5.0), and firm texture (score 4.0). In contrast, peppers stored without packaging exhibited significant deterioration, primarily due to fungal infection by Fusarium sp. and Aspergillus sp. Overall, the findings demonstrate that vacuum packaging combined with low-temperature storage effectively extends the shelf life of cayenne pepper while preserving its physical, nutritional, and sensory attributes.